THE WOOD MARKET IN THE BRASOV – COVASNA AREA (II): THE ATTRACTIVENES OF THE OFFER - Niculaie ANTONOAIE; Cristina ANTONOAIE; Victor ANTONOAIE (Pro Ligno, 2015)
This is the second part of the paper concerning the Brasov-Covasna wood market (Part I: Behavior of Firms in Auction). This paper continues the analysis of company behavior and the attractiveness in the field of wood-felling at auctions organized between 2012 and 2013 in the studied area for timber sourced from special protection forests. Here we will present the derived indicators which were used to study company behavior at auctions and the results obtained by analyzing these indicators. As was the case for the first paper we have found significant differences in the behavior of companies taking part in these auctions compared to those bidding for wood in general production forests